2011
DOI: 10.4304/jcp.6.9.1819-1824
|View full text |Cite
|
Sign up to set email alerts
|

The research on the influencing factors of financing strategy of woman entrepreneurs in China

Abstract: <p class="Abstract">Based on the data from the nationwide surveys of SMEs in "China's Private Economic Research in 2002, this paper examines gender differences among Chinese entrepreneurs seeking financing pattern, including external and internal financing, and studies on the factors those affect women entrepreneurs&rsquo; financing strategies through theoretical analysis and model validation from the human capital and social capital perspective. We find that human capital and social capital have pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
6
0
4
Order By: Relevance
“…The majority of the research on this topic reported that obtaining adequate financial support is a common problem encountered by women-led enterprises, as noted earlier (e.g. Li, Tang, and Liu 2016;Tan 2008;Xiong et al 2011;Zhang and Pan 2012). On the other hand, Hussain et al (2010) argue that women seem to be no more disadvantaged from obtaining finance than men in China and, in some aspects, appear to be in a better position.…”
Section: Entrepreneurial Processmentioning
confidence: 84%
“…The majority of the research on this topic reported that obtaining adequate financial support is a common problem encountered by women-led enterprises, as noted earlier (e.g. Li, Tang, and Liu 2016;Tan 2008;Xiong et al 2011;Zhang and Pan 2012). On the other hand, Hussain et al (2010) argue that women seem to be no more disadvantaged from obtaining finance than men in China and, in some aspects, appear to be in a better position.…”
Section: Entrepreneurial Processmentioning
confidence: 84%
“…First, our findings confirm that there exists gender gap in both formal financing and informal financing under Chinese context. Existing gender-financing research studies under Chinese context focus more on informal financing (Mu et al, 2017;Sheng and Mendes-Da-Silva, 2014;Xiong et al, 2011) instead of formal financing. Based on the data collected from China, after controlling the entrepreneur and firm-related characteristics, we verified that both formal and informal financing are influenced by gender factors.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…In France, there is a similar situation: only 10% of French female entrepreneurs prefer bank financing, a third lower than male entrepreneurs (Orhan, 2001). Also, research in China in Vietnam has confirmed that male entrepreneurs prefer using external financing more than female entrepreneurs (Xiong et al , 2011; Zhu et al , 2019).…”
Section: Female Entrepreneurs’ Financing Sourcesmentioning
confidence: 95%
“…Women tend to avoid financial institutions, such as banks, that traditionally have been a key source for entrepreneurship financing (Buttner and Rosen, 1988; Carter et al , 2007; Hertz, 2011; Xiong et al , 2011). But the COVID-19 crisis has increased banks’ vulnerability because of risks related to deposits, withdrawals and non-performing loans (Goodell, 2020; Nseobot et al , 2020).…”
Section: Female Entrepreneurs’ Financing Sourcesmentioning
confidence: 99%